The Demographics of Canine Hip Dysplasia in the United States and Canada. (12th March 2017) - Loder, Randall T.; Todhunter, Rory J.
Abstract : Canine hip dysplasia (CHD) is a common problem in veterinary medicine. We report the demographics of CHD using the entire hip dysplasia registry from the Orthopedic Foundation for Animals, analyzing differences by breed, sex, laterality, seasonal variation in birth, and latitude. There were 921, 046 unique records. Each dog was classified using the American Kennel Club (AKC) and Fédération Cynologique Internationale (FCI) systems. Statistical analysis was performed with bivariate and logistic regression procedures. The overall CHD prevalence was 15.56%. The OR for CHD was higher in females (1.05), those born in spring (1.14) and winter (1.13), and those in more southern latitudes (OR 2.12). Within AKC groups, working dogs had the highest risk of CHD (OR 1.882) with hounds being the reference group. Within FCI groups, the pinscher/molossoid group had the highest risk of CHD (OR 4.168) with sighthounds being the reference group. The similarities between CHD and DDH are striking. Within DDH there are two different types, the typical infantile DDH and the late onset adolescent/adult acetabular dysplasia, with different demographics; the demographics of CHD are more similar to the later onset DDH group. Comparative studies of both disorders should lead to a better understanding of both CHD and DDH.